PERAN UNITED NATIONS INDUSTRIAL DEVELOPMENT ORGANIZATION (UNIDO) DALAM MEMBANTU PERKEMBANGAN INDUSTRI MANUFAKTUR INDONESIA 2010-2013 - Bonny Desfiando; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research aims to determine the role of the UNITED NATIONS INDUSTRIAL DEVELOPMENT ORGANIZATION (UNIDO) in assisting development of the manufacturing industry in Indonesia. Type of this research is descriptive analysis. Industrial development in the era of globalization requires right and consistent strategy, so that the industry can realize a strong and competitive in both the domestic market and in the global market, which will be able to drive economic growth, create jobs, increase incomes and reduce poverty in Indonesia. The writer tries to describe and explain the role of UNIDO in terms of helping develop the Indonesian manufacturing industry.Sources obtained through the literature review, other books, internet, etc.. Source analysis is a qualitative research analysis, This research uses a level analysis of international organizations, use perspective that describes the state of pluralism is not the only rational actors in international relations. Uses non states actors, using the theory that describes the role of guidance that is given structurally.The conclusion of this research conducted by UNIDO's role in assisting the development of Indonesia's manufacturing industry. UNIDO's role in poverty reduction through productive activities, trade capacity building, productive use of energy and energy efficiency as well as environmental management.Keywords : UNIDO, role, industry, development and manufacturing